PEREMPUAN DALAM BINGKAI HAK ASASI MANUSIA DALAM HUKUM KELUARGA ISLAM - Tahir, Masnun (Musawa Jurnal Studi Gender dan Islam, 2016)
This article intends to portray the idea that Islam came with the mission of returning for women’s right that have been looted and pillaged by men during the days of ignorance, in addition to showing that Islam elevate the dignity of women and give back rights that have been shattered and trampled by the domination of men and destroyed by the religious traditions and national fanaticism of a narrow group. With the specific terminology of family law concerning women’s right -a noble endeavor in itself- this article explains the relationship between maqasih sharia and human rights, with a special focus on the implementation of human rights. On the other hand this paper also analyses the implementation of women’s rights in Islamic family law.